FORMATION OF INFORMATION COMPETENCE OF A MODERN EDUCATOR (Web of Teachers: Inderscience Research, 2024)
This study is devoted to studying the process of developing information competence in modern educators. The purpose of the study is to identify factors influencing the development of information competence of educators in the context of modern educational requirements and digitalization of society. The concept of “teacher information competence” was developed, including its structure and composition. The levels of formation of components of information competence and the levels of teacher readiness as a whole were investigated. It turned out that information competence occupies an important place in the formation of general, cultural, personal and professional competencies among teachers. It is expressed in the specialist’s ability to work with information, information and digital technologies, information resources, interactive and multimedia equipment, as well as in the use of innovative forms and methods of organizing the educational process.